2022
DOI: 10.5093/clysa2022a2
|View full text |Cite
|
Sign up to set email alerts
|

Emotional Problems in Spanish Children and Adolescents during the COVID-19 Pandemic: A Systematic Review

Abstract: As a result of the COVID-19 pandemic, the population has been exposed to a high level of stress. The alarm state decreed in Spain in March 2020 limited movement and suspended various activities such as school attendance (Real Decreto 463/2020). From that moment on, a particularly restrictive and lasting confinement began compared to other European countries, with Spanish children not being allowed to leave home until six weeks later .Confinement during the pandemic has had effects on various aspects of childre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 47 publications
1
9
1
1
Order By: Relevance
“…In adolescents, no significant differences were found in emotion regulation, nightmares, or suicide risk pre- vs. during the pandemic. Although studies have shown emotional deterioration ( Ravens-Sieberer et al, 2021 ) and an increase in emotion regulation problems ( Amoros-Reche et al, 2022 ) among children and adolescents during the pandemic ( Ravens-Sieberer et al, 2021 ), our findings do not show a significant increase. This adolescent sample admitted to the inpatient psychiatric program with significantly high emotional problems score pre-pandemic leading to a ceiling effect.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In adolescents, no significant differences were found in emotion regulation, nightmares, or suicide risk pre- vs. during the pandemic. Although studies have shown emotional deterioration ( Ravens-Sieberer et al, 2021 ) and an increase in emotion regulation problems ( Amoros-Reche et al, 2022 ) among children and adolescents during the pandemic ( Ravens-Sieberer et al, 2021 ), our findings do not show a significant increase. This adolescent sample admitted to the inpatient psychiatric program with significantly high emotional problems score pre-pandemic leading to a ceiling effect.…”
Section: Discussioncontrasting
confidence: 99%
“…Youth are also at a particularly heightened risk for the psychological effects of COVID-19 due to their developmental stage ( Lamblin et al, 2017 ). The pandemic has been associated with increased youth depression and anxiety symptoms ( Duan et al, 2020 ; Ma L et al, 2021; Magson et al, 2020 ; Racine et al, 2021 ; Xie et al, 2020 ; Zhou et al, 2020 ), increased rates of suicide ideation and attempts ( Hill et al, 2021 ), increased sleep problems (Ma L et al, 2021;), increased presentation of posttraumatic stress symptoms (Ma L et al, 2021), significant sleep problems ( Ravens-Sieberer et al, 2021 ), an increase in emotion regulation problems ( Amoros-Reche et al, 2022 ; Ravens-Sieberer et al, 2021 ) and a significant decrease in life satisfaction among youth ( Magson et al, 2020 ). Parents also report their children are experiencing significantly increased irritability, worry, sleep disorders, fatigue, and agitation coinciding with COVID-19 ( Jiao et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…These variables were also reported in studies carried out on the general population, both in Spain ( Berasategi et al, 2021 ; Amorós-Reche et al, 2022 ) and internationally ( Pisano et al, 2020 ; Bignardi et al, 2021 ; Ravens-Sieberer et al, 2021 ; Weissman et al, 2021 ; Wright et al, 2021 ).…”
Section: Discussionsupporting
confidence: 52%
“…Also in Spain, in a recent review by Amorós-Reche et al (2022) , it was concluded that mental health problems increased overall during confinement; Berasategi et al (2021) compiled information, after 3–4 weeks of confinement, from 1,046 Spanish parents with children between 2 and 14 years old, finding that 74.66% were more angry than usual, 55.54% cried more, 70.17% were more nervous, and 35.95% suffered more nightmares.…”
Section: Introductionmentioning
confidence: 99%
“…Studies investigating the prevalent emotions experienced by children during periods of social restrictions found high rates of sadness, fear, boredom, nervousness, loneliness, sadness and anger [ 18 , 19 , 20 , 21 , 22 , 23 ]. Regarding parents’ perspectives, Orgiles et al [ 24 ] found that 85.7% of parents perceived changes in their children’s emotional state and behaviors during the quarantine, and the most frequent symptoms were difficulty concentrating (76.6%), boredom (52%), irritability (39%), restlessness (38.8%), nervousness (38%), feelings of loneliness (31.3%), uneasiness (30.4%) and worries (30.1%).…”
Section: Introductionmentioning
confidence: 99%